Mount Mitchell and the Black Mountains : an environmental history of the highest peaks in eastern America - Silver, Timothy, 1955- (University of North Carolina Press, 2003)
This volume looks at the natural and human history of North Carolina's Mount Mitchell, part of the Black Mountain range and the highest peak in the United States. It chronicles the geological forces that created this landscape, traces its environmental change and human intervention.